2004
DOI: 10.1541/ieejpes.124.1317
|View full text |Cite
|
Sign up to set email alerts
|

The Simultaneous Design of Multiple Power System Stabilization Controllers Using the System Identification and the Non-linear Optimization Technique

Abstract: We have developed a simultaneous control design method for multiple power system stabilization controllers such as PSSs using the system identification and the non-linear numerical optimization technique. The developed controller design can take into consideration of controller structure and several design constrains in the controller design. For multiple controllers design, a reduced order MIMO linear system, which show similar dynamic properties to some original full order power systems, is identified from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…2. The objective of this study was to obtain an identified model to be used in the MPM method [1,2,5]. For the model output, we used the active power P and the frequency ω of every generator.…”
Section: Input-output Of Identified Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…2. The objective of this study was to obtain an identified model to be used in the MPM method [1,2,5]. For the model output, we used the active power P and the frequency ω of every generator.…”
Section: Input-output Of Identified Modelmentioning
confidence: 99%
“…Power network models on simulator that is, the active power P and frequency ω of every generator, are input to the target PSSs, compensated for phase lead-lag and gain, and then input to the model AVRs. The objective of this study was to obtain an identified model to be used in the MPM method [1,2,5]. The MPM method has the distinctive characteristic that the lead-lag constants and gains are set in coordinated fashion so as to optimize the damping of the closed loop composed of the PSS and the identified model; therefore, pole placement must be identified precisely for proper evaluation of the damping variation.…”
Section: Input-output Of Identified Modelmentioning
confidence: 99%
See 2 more Smart Citations